Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To square the binomial [tex]\((8y - 5)^2\)[/tex], we use the formula for the square of a binomial [tex]\((a - b)^2\)[/tex]. The formula is given by:
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
Here, [tex]\(a = 8y\)[/tex] and [tex]\(b = 5\)[/tex].
1. Square the first term:
[tex]\[ a^2 = (8y)^2 = 64y^2 \][/tex]
2. Multiply the first term by the second term and then by 2:
[tex]\[ -2ab = -2 \cdot (8y) \cdot 5 = -80y \][/tex]
3. Square the second term:
[tex]\[ b^2 = 5^2 = 25 \][/tex]
Now, combining these results, we get:
[tex]\[ (8y - 5)^2 = 64y^2 - 80y + 25 \][/tex]
So the expanded form of the binomial [tex]\((8y - 5)^2\)[/tex] is:
[tex]\[ 64y^2 - 80y + 25 \][/tex]
Thus, the correct answer is:
[tex]\[ 64y^2 - 80y + 25 \][/tex]
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
Here, [tex]\(a = 8y\)[/tex] and [tex]\(b = 5\)[/tex].
1. Square the first term:
[tex]\[ a^2 = (8y)^2 = 64y^2 \][/tex]
2. Multiply the first term by the second term and then by 2:
[tex]\[ -2ab = -2 \cdot (8y) \cdot 5 = -80y \][/tex]
3. Square the second term:
[tex]\[ b^2 = 5^2 = 25 \][/tex]
Now, combining these results, we get:
[tex]\[ (8y - 5)^2 = 64y^2 - 80y + 25 \][/tex]
So the expanded form of the binomial [tex]\((8y - 5)^2\)[/tex] is:
[tex]\[ 64y^2 - 80y + 25 \][/tex]
Thus, the correct answer is:
[tex]\[ 64y^2 - 80y + 25 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.